Sesquiterpenes from Ambrosia artemisiifolia and their allelopathy - Liu, Zhixiang; Zhang, Nan; Ma, Xiaoqing; Zhang, Tong; Li, Xuan; Tian, Ge; Feng, Yulong; An, Tong (Frontiers in Plant Science, 2022)
Ambrosia artemisiifolia, an invasive plant, has seriously harmed the agricultural production, native ecosystems and human health. Allelopathy is an important reason for the successful invasion of this alien plant. However, the chemical basis, action effects, action mechanism and release pathway of its allelopathy remain unclear. To address these problems, four sesquiterpenes (1–4), consisting of three new sesquiterpenes (1–2, 4), were isolated from the whole plant of A. artemisiifolia using a variety of column chromatography techniques, and identified using HR-ESIMS, 1D-NMR, 2D-NMR, and ECD. All the compounds exhibited different levels of inhibitory effects on three native plants (Setaria viridis, Digitaria sanguinalis, Chenopodium album) and one model plant (Arabidopsis thaliana), especially compound 1. In addition, the preliminary action mechanism of active compound 1 was revealed by FDA/PI staining assay. Furthermore, the allelopathic substances 1–3 were released into environment through the root secretion pathway by UPLC-MS/MS analyses.